Mapping the transition from arithmetic to algebra: a bibliometric and structural review (2003–2023) - Victoria Alejandra García Fajardo; Diana Carolina Burbano González; Cristhian Leonardo Urbano-Leon (Frontiers in Education, 2025)
The shift from arithmetic to algebra entails significant cognitive and pedagogical challenges for both students and teachers. Despite its importance in early mathematics education, few systematic reviews have comprehensively examined the scientific literature on this transition using both quantitative and structural lenses. This study addresses that gap by conducting a bibliometric and structural analysis of 127 academic publications from 2003 to 2023, sourced from the Web of Science and Scopus databases. The review followed PRISMA guidelines and incorporated text mining techniques to harmonize metadata across sources. Graph theory tools were employed to map collaborative networks and thematic clusters, while the Tree of Science model organizes the literature into roots, trunk, and branches to visualize the intellectual development of the field and to identify foundational works, central contributions, and emerging lines of research. The results highlight a growing academic interest in early algebra and algebraic thinking, viewed as essential pedagogical approaches to confront the conceptual hurdles of transitioning from arithmetic. Key thematic areas, leading scholars, and influential research groups were identified, with the United States standing out as the dominant contributor in the field. This review offers relevant insights for researchers, educators, and education policymakers aiming to enhance the teaching and learning of algebra by building on its arithmetic roots and understanding the evolving scholarly landscape.